The observance of maternal rights charter in labor with postpartum anxiety in mothers delivering at maternity hospitals - Marziye Shahpari; Mahnaz Zarshenas; Marzieh Akbarzadeh (Medicina Clínica Práctica)
Introduction: One of the effective factors in reducing postpartum mental illnesses, such as anxiety, is observing maternal rights and mothers' positive attitude about childbirth. The present study aimed to determine the relationship between maternal rights charter observance during labor and postpartum anxiety. Materials and methods: This was a cross-sectional study. We investigated the observance of maternal rights charter using a researcher-made questionnaire. Postpartum anxiety was investigated using Spielberger questionnaire. The relationship between these 2 factors was investigated via studying 160 eligible pregnant mothers admitted in Hazrat Zeinab, Hafez, and Shooshtari hospitals. Data were analyzed through SPSS software (version 16), using one-way ANOVA and Pearson correlation coefficient at the significant level of 5%. Results: There a was a significant relationship between the delivery team members in terms of dimensions in the maternal rights charter (p=.003) and general dimensions (p=.001). This difference was in emotional (p=.001) and informational (p=.013) dimensions. There was no significant difference in physical dimension (p=.070). Among the participants, 93.75% had implicit anxiety and 83.75% had explicit anxiety. Conclusions: Failure to observe maternal rights charter was associated with an increase in explicit and implicit postpartum anxiety. Maternal rights in the physical aspect were observed equally by the midwife instructor, staff, and residents. However, there was a difference in the emotional and informational dimensions of the members of the delivery team. Resumen: Introducción: Uno de los factores eficaces para reducir las enfermedades mentales posparto, como la ansiedad, es el respeto de los derechos maternos y la actitud positiva de las madres ante el parto. El propósito de este estudio fue determinar la relación entre la observancia de la Carta de Derechos Maternos durante el parto y la ansiedad posparto. Materiales y Métodos: Este es un estudio transversal. Investigamos la observancia de la carta de derechos maternos utilizando un cuestionario elaborado por un investigador; La ansiedad posparto se investigó mediante el cuestionario de Spielberger. Además, se investigó la relación entre estos dos factores en 160 madres embarazadas ingresadas en los hospitales Hazrat Zeinab, Hafez y Shooshtari y fueron elegibles para su inclusión. Los datos se analizaron mediante el software SPSS (versión 16), utilizando ANOVA unidireccional y coeficiente de correlación de Pearson al nivel significativo del 5%. Resultados: Entre los integrantes del equipo de parto en cuanto a las dimensiones de la carta de derechos maternos (p = 0,003) y dimensiones generales (p = 0,001) fue significativa. Esta diferencia se produjo en las dimensiones emocional (p = 0,001) e informativa (p = 0,013). No hubo diferencia significativa en la dimensión física (p = 0,070). El 93,75% de los participantes en este estudio tenía ansiedad implícita y el 83,75% tenía ansiedad explícita. Conclusiones: El incumplimiento de la carta de derechos maternos se asoció con un aumento de la ansiedad posparto explícita e implícita. Los derechos maternos en el aspecto físico fueron respetados por igual por la partera instructora, el personal y los residentes. Sin embargo, hubo una diferencia en las dimensiones emocional e informativa de los miembros del equipo de entrega.